CONSEQUENCES OF SALINIZATION ON CARBON AND NUTRIENT RELEASE FROM A RESTORED COASTAL FORESTED WETLAND - Goehrig, Tori J (East Carolina University, 2016)
Given that wetlands provide important ecosystem services, such as improving water quality and protecting inland regions from storms, it is necessary to understand how sea level rise and climate change will alter their structure and function. Wetlands play an important role in the global carbon cycle, thus much work has focused on how they will respond to climatic change. One aspect that has not received much attention is how increasing salinity, due to drought and sea level rise, alters the export of dissolved organic carbon and the process of flocculation. This study combined long-term field observations, laboratory assays, and a field experiment to examine the effects of salinity on the process of flocculation and the subsequent fate of particulate organic carbon (POC). I compiled long-term field data to determine control mechanisms on POC concentration. To assess the effects of salinity and floc reversibility, I conducted a lab assay. I also conducted a field saltwater addition with adapted sediment traps to determine if salt induced flocculation and changes in water clarity and nutrients. I then determined the bioavailability of the floc for heterotrophic microbial respiration. In the long-term field data, salinity did not enter the site and POC formation was variable and was weakly correlated to nitrate. In the lab assays, salinity induced POC formation and resulted in an increase in light penetration, and the floc did not re-dissolve after a simulated storm event. In the field experiment, salt addition induced flocculation and established a potential mechanism for phosphorus retention. DOC was converted to recalcitrant POC, reducing bioavailability for microbial respiration, which led to increased floc deposition. Salinity mobilized nitrogen and stimulated algal biomass production. My results suggest that saltwater intrusion could increase organic sediment accumulation in wetlands with high DOC loads and increase the potential for algal blooms in legacy impacted wetlands with low flows. My results suggest that increased salinity to freshwater wetlands could reduce carbon export and increase soil accretion rates, increasing ecosystem resilience to low salinity perturbations.
Keywords: Climate Change; Nutrient Release; Particulate Organic Carbon; Storms; Wetland ecology; Saltwater encroachment; Wetlands--Effect of drought on; Sea level; Flocculation